Optical imaging of mice in oncologic research. Issue 5 (1st October 2004) - Citrin, Deborah; Camphausen, Kevin
Optical imaging is a highly sensitive technique for detecting a variety of cellular, molecular and tissue processes in vivo and in vitro. Optical imaging systems are well suited to in vivo imaging in the laboratory setting for a variety of reasons, including low cost, ease of use and efficiency of imaging. Commercial availability of optical imaging detector systems has allowed more investigators to explore their use for a variety of applications. The ever-increasing number of naturally occurring and modified near-infrared probes, photoproteins, and fluorescent probes provide opportunities to improve detection and labeling. Technical advances in detector systems and imaging software have allowed the refinement of established techniques. Furthermore, the availability of mice genetically altered to express photo and fluorescent proteins have spurred tremendous growth in this area of research.